Comparison of hybrid membrane aerated biofilm reactor (MABR)/suspended growth and conventional biological nutrient removal processes - Avery L. Carlson (IWA Publishing, 2021)
Mathematical modelling was used to investigate the possibility to use membrane aerated biofilm reactors (MABRs) in a largely anoxic suspended growth bioreactor to produce the nitrate-nitrogen required for heterotrophic denitrification and the growth of denitrifying phosphorus accumulating organisms (DPAOs). The results indicate that such a process can be used to achieve a variety of process objectives. The capture of influent biodegradable organic matter while also achieving significant total inorganic nitrogen (TIN) removal can be achieved with or without use of primary treatment by operation at a relatively short suspended growth solids residence time (SRT). Low effluent TIN concentrations can also be achieved, irrespective of the influent wastewater chemical oxygen demand (COD)/total nitrogen (TN) ratio, with somewhat larger suspended growth SRT. Biological phosphorus and nitrogen removal can also be effectively achieved. Further experimental work is needed to confirm these modelling results. HIGHLIGHTS Hybrid MABRs can achieve lower effluent TIN concentrations, and more carbon capture, at lower SRTs than conventional systems.; Influent carbon composition affects denitrification, but modelling shows better performance in hybrid MABR systems.; Primary treatment benefits carbon capture, but can be eliminated depending on treatment goals.; Combined biological nitrogen and phosphorus removal is possible and improved in hybrid MABRs.;